Facile synthesis of N-doped carbon-coated Si/Cu alloy with enhanced cyclic performance for lithium ion batteries. Issue 81 (16th August 2016) - Deng, Libo; Zhang, Wei; Ren, Xiangzhong; Zhang, Peixin; Li, Yongliang; Sun, Lingna; Gao, Yuan
Abstract : Nanoparticles consisting of silicon/copper/nitrogen-doped-carbon (Si/Cu/N–C) with a Si/Cu alloy core and a N–C shell have been prepared and their cyclic life as an anode in lithium-ion batteries was significantly enhanced compared to Si/Cu alloy. Abstract : Nanoparticles consisting of silicon/copper/nitrogen-doped-carbon (Si/Cu/N–C) with a Si/Cu alloy core and a N–C shell have been synthesized by a two-step process, including the preparation of a Si/Cu alloy via mechanical ball milling and the preparation of Si/Cu/polydopamine (PDA) through in situ polymerization of dopamine followed by carbonization at 850 °C. Their microstructures and their electrochemical performance as an anode in lithium-ion batteries (LIB) were investigated. The composite nanoparticles show a coulomb efficiency of 74% in the first cycle and a discharge capacity of 851 mA h g −1 in the second cycle. They still retain 89% of their second-cycle capacity after 100 cycles at a current density of 0.08 mA cm −2 . These results are superior to those for a Si/Cu alloy without the carbon coating, which is thought to be due to the carbon layer being able to mitigate the volume change of silicon and the nitrogen-doping can further enhance the wettability and electrical conductivity of the electrode material.